When to remove the drainage catheter in patients with percutaneous cholecystostomy? - Kayaoglu,Sevcan Alkan (2022)
SUMMARY OBJECTIVE: The treatment for patients with acute calculous cholecystitis who have high surgical risk with percutaneous cholecystostomy instead of surgery is an appropriate alternative choice. The aim of this study was to examine the promising percutaneous cholecystostomy intervention to share our experiences about the duration of catheter that has yet to be determined. METHODS: A total of 163 patients diagnosed with acute calculous cholecystitis and treated with percutaneous cholecystostomy between January 2011 and July 2020 were reviewed retrospectively. The Tokyo Guidelines 2018 were used to diagnose and grade patients with acute cholecystitis. RESULTS: The mean age was 71.81±12.81 years. According to the Tokyo grading, 143 patients had grade 2 and 20 patients had grade 3 disease. The mean duration of catheter was 39.12±37 (1-270) days. Minimal bile leakage into the peritoneum was noted in 3 (1.8%) patients during the procedure. The rate of complications during follow-up of the patients who underwent percutaneous cholecystostomy was 6.9% (n=11), and the most common complication was catheter dislocation. Cholecystectomy was performed in 33.1% (n=54) of the patients at follow-up. Post-cholecystectomy complication rate was 12.9%. At the follow-up, the rate of recurrent acute cholecystitis episodes was 5.5%, while the mortality rate was 1.8%. The length of follow-up was five years. CONCLUSIONS: The rate of recurrence was significantly higher among the patients with catheter for <21 days. We recommend that the duration of catheter should be minimum 21 days in patients undergoing percutaneous cholecystostomy.